Analisis Faktor Risiko Kontaminasi Entamoeba histolytica pada Air Sumur Masyarakat di Desa Paya Leupah, Kecamatan Simpang Keramat, Aceh Utara - Tita Aulia Putri; Rizka Sofia; Mohammad Mimbar Topik (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Entamoeba histolytica is an intestinal protozoan that can cause diarrhea through fecal–oral transmission due to the consumption of food or water contaminated with parasitic cysts. Based on data from the Badan Pusat Statistik in 2017–2019, Simpang Keramat District, particularly Paya Leupah Village, still had limited access to clean water and low ownership of permanent sanitary latrines, which may increase the risk of environmental contamination. This study aimed to analyze the characteristics of dug wells and the risk factors associated with Entamoeba histolytica contamination in community well water. An observational analytic study with a cross-sectional design was conducted on 50 dug wells selected using purposive sampling. Data were obtained through field observations and laboratory examinations of well water samples. The results showed that most wells had distances to septic tanks that did not meet health standards (58%) and inadequate well floor conditions (82%), while the majority of wells had depths that fulfilled the recommended standard (76%). All well water samples tested negative for Entamoeba histolytica cysts; therefore, the association between risk factors and contamination could not be determined.